Multilingualism and multiliteracy in primary education in India: A discussion of some methodological challenges of an interdisciplinary research project. (March 2019) - Tsimpli, Ianthi; Mukhopadhyay, Lina; Treffers-Daller, Jeanine; Alladi, Suvarna; Marinis, Theodoros; Panda, Minati; Balasubramanian, Anusha; Sinha, Pallawi
In the Indian context, concerns have been raised for many years about the learning outcomes of primary school children. The complexity of the issue makes it difficult to advise stakeholders on what needs to be done to improve learning in primary schools in India. As it has been shown that low socio-economic status is one of the key factors that negatively affect learning outcomes, the focus of the Multilila project ('Multilingualism and multiliteracy: Raising learning outcomes in challenging contexts in primary schools across India') is on educational achievement among children of low socio-economic status. In following the development of language, literacy, maths and cognitive abilities of primary school children over two years we hope to throw new light on why multilingual children in India do not always experience the cognitive advantages associated with multilingualism in other contexts. This paper focuses on some of the methodological challenges faced by this project. After explaining the rationale for the study, we sketch the contribution this project can make to the discussion about cognitive advantages of bilingualism. We then focus on the Indian context before presenting the methodology of the project (design, participants, instruments and procedure). Finally, we summarize the key challenges for the project and possible solutions to those challenges, and present an outlook towards the future.